Photo journals with refugee youth: Methodological reflections of conducting research during the pandemic - Gonzalez, Emilia; Ruiz-Casares, Monica (Alterstice)

(untitled) (Alterstice, 2022)
The use of visual methods as a research tool has increased worldwide, along with the need to understand the nuanced and contextual benefits, challenges, and risks of their use. Based on participatory approaches, visual methods can offer an adaptable, interactive, and critical way of engaging with refugee young people, making research more accessible and representative. In Montreal, the COVID-19 pandemic forced programs, services and research involving refugee young people to adapt to meet the needs of this population while respecting physical distancing guidelines. Little is known about the strengths and challenges of using visual methods in the context of physical distancing, especially with refugee young people. In this paper, we describe some of the strengths and challenges of using photo journals, a form of visual methods, with refugee young people (11-17 years old) to document their experiences participating in Say Ça!, a Montreal community-based mentoring program, during the pandemic. Six young people participated in photo journals and individual interviews, and 11 volunteers participated in focus group discussions. The journals prompted young people to describe themselves, their favourite moments at Say Ça! and moments when things did not go as planned. In the findings, we describe opportunities and challenges of using photo journals to engage migrant young people in research during the pandemic. Photo journals facilitated building a rapport with young people, overcoming communication challenges, ensuring valid consent throughout the study, and addressing power dynamics between participants and researchers. Challenges included recruitment, confidentiality, and study logistics. In this paper, we present key lessons learned from using photo journals as a method to capture the perspectives of refugee young people. We argue that by including the views of service users, programs may gain a richer understanding of the elements that contribute to refugee young people wellbeing and, ultimately, help improve community-based support for this population in Montreal and other welcome programs.